Impact of Anthropogenic and Natural Disturbances on Biodiversity Patterns of Macroinvertebrates at different Taxonomic Levels in African Freshwater Systems - Dusabe, Marie Claire; Justus Liebig University Giessen (My University, 2025)
African freshwater ecosystems are subject to both natural and anthropogenic pressures that affect habitat quality, biodiversity, and ecosystem functioning. Macroinvertebrates have been used in routine bioassessments to detect disturbances for decades. However, it is unclear how accurately they reflect disturbances at different taxonomic levels. This thesis investigates the environmental impact of disturbances in selected East African freshwater ecosystems, and how macroinvertebrates respond to these changes at different temporal and spatial scales. The effects of dam construction and the effectiveness of family-level bioindication for detecting them were tested on the Ruzizi River. Multimetric indices (MMIs) were used in Lake Kivu to assess their ability to identify and distinguish between various environmental pressures. Mollusc community indices were used to assess long-term environmental changes in six Albertine volcanic lakes. Additionally, the freshwater snail Gabbiella was tested as a model taxon to reconstruct historical hydrological shifts and water level fluctuations across the African Great Lakes, major connected river systems, and the crater lakes of western Uganda based on phylogenetic and biogeographical analyses. Finally, an eDNA index was used at Lake Albert to test its applicability in biodiversity surveys and use in African freshwater biomonitoring systems. The results showed that on the Ruzizi River, family-level indi-cators did not adequately capture the impact of the dams, while on Lake Kivu multimetric indices more effectively distinguished between stressed and reference sites. Pollution patterns varied across the lake, with greater impacts in the northern basin than in the central and southern basins. Phylogenetic and biogeography indices proved useful in detecting historical disturbances. The diversification of Gabbiella mirrored earlier water-level changes, a trend also reported in other African molluscs and fish groups. A series of vicariance and dispersal events shaped the biogeographic history of Gabbiella humerosa, and allowed tracing historical drainage changes during the Pleistocene. However, eDNA analysis yielded limited records of macroinvertebrates, as plankton dominated because only surface water was sampled. The lack of a reference library makes it difficult to accurately assign eDNA sequences. Nevertheless, the results underscore the potential of using aquatic eDNA for taxonomy-free biomonitoring in tropical regions. The results of the historical molluscan biodiversity change in the six volcanic barrier lakes studied in this thesis show that new species have emerged and others have disappeared over time. Invasive taxa were common, with crayfish and non-native snails among those displacing native species. The biogeography of most Albertine volcanic barrier lakes exhibits a Nilotic affinity, except for invasive species and other taxa with wide distributions. The current findings provide a useful basis for conservation efforts and inform strategies to slow the ongoing loss of biodiversity.
Keywords: Freshwater ecology; African Great Lakes; Taxonomic surrogacy; Biomonitoring; Macroinvertebrates; Freshwater conservation; ddc:500